CRIMINALS' RESPONSE TO CHANGING CRIME LUCRE. - Shoukry, George F. N. (Economic Inquiry, 2016)
How do criminals respond to changes in the benefit from committing a successful crime? This question is relevant for understanding the effectiveness of crime-fighting policies that reduce demand for illegal goods, disrupt black markets, and otherwise eliminate cheaper avenues to illicit gain. However, the literature has not sufficiently addressed this question, partly because finding a reliable measure of crime lucre is difficult. Using proprietary data on cargo theft, I match historical prices of various goods with their thefts and estimate the price elasticity of theft to be 1.225 over a cumulative 7-month horizon. ( JEL K42)